ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBUATAN KEPUTUSAN KONSUMEN DALAM MEMBELI SUSU BUBUK INDOMILK - Indriyati, Indriyati; Wibowo, Yudho (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2015)
Powder milk product experienced the enough impressive growth slowlycomparing to the economic crisis time happened since the middle of 1997. Thiswas supported with the more and more increase of people awareness of requiringthe nutrient and healthy. The demand was more and more increase to support theexisting company to enlarge the total of production resulted. Seeing the muchenough number of powder milk producers, the competition in the powder milkindustry is tight enough. Based on the case so that it needed to be identified thevarious factors influencing the decision of consumer purchase toward the powdermilk. The brand used as the research object was the brand of Indomilk powdermilk.The goals of this research were (1) to find out the factors significantly influencedthe consumer decision making in buying the Indomilk powder milk, and (2) to findout the difference of factors influencing the consumer behavior in doing decisionpurchase the powder milk product of Indomilk based on the different type ofgender, age, job, and the expense per month. The tool of data analysis used in thisresearch was the multiple regression analysis and the chi square test. Themultiple regression analysis was aimed to find out the significant factorsinfluencing to the consumer decision making in buying the powder milk ofIndomilk. The chi square test was aimed to find out the difference of factorsinfluencing the consumer decision making based on the type of gender, age, job,and the expense per month of consumer.The result of research showed of factor significantly influencing the consumerdecision making in purchasing the powder milk of Indomilk were thecharacterisric factor of individual consumer and the influence of marketingstrategy. Meanwhile the factor of environmental influence was not significant toinfluence the consumer decision making.Based on the chi square test, it was known there was not the difference of factorsinfluencing the decision of consumer purchase based on the type of gender, age,job, and the expense per month. How ever, based on age it was known there werethe difference of factors that influencing the decision of consumer purchase thatwere demography and culture factors.